Using Artificial Intelligence in the Study of Contemporary History and Psychology to Improve the Quality of Higher Education - Dalal Al-Suri; Salma Abu Sneina (AlQalam Journal of Medical and Applied Sciences, 2025)
Higher education is undergoing rapid transformations driven by technological advancement. However, the application of artificial intelligence (AI) in the humanities—such as contemporary history and psychology—remains limited. This study aims to explore the role of AI in developing teaching methods and analytical approaches within these two disciplines, focusing on the period from 1945 to 2025. The study adopts a descriptive and analytical methodology by reviewing relevant literature and examining tools such as historical text analysis and behavioral modeling. The results indicate that integrating AI enhances student engagement, fosters critical thinking, and supports deeper understanding of both psychological and historical subjects. The study emphasizes the importance of incorporating such technologies into university curricula, while providing specialized training for faculty and students and reinforcing the necessary technological infrastructure. It further recommends adopting flexible educational policies that keep pace with digital transformation and contribute to improving the quality of higher education in the humanities